The process of adaptation of catholicism to indigenous cultures in southeast ASIA (the case of catholicism in Philippines and Vietnam) - Vũ, Văn Đạt (2021)
Catholicism antered the Philippines and Vietnam sice the 16 century, At first, civilization class occurred but Catholicism gradually adapted to the local culture. catholicism in the Philippined and Vietnam nowadays is the product pff a long - lasting proces of fight and adaptation in order to confirm its posotion as important part of caultural life of each country.